Disaster Prevention Strategy at Gelora Bung Karno Main Stadium from the Perspective of the Police Role - Fajar, Mohamad; Warno Utomo, Suyud; Achjani Zulfa, Eva (Sekolah Tinggi Ilmu Kepolisian, 2025)
Disaster risk is formed by the interaction of hazards with a vulnerable community. Risks arising from intentional hazards are generally more predictable than those from natural and technological causes. Therefore, when a hazard is predictable, a disaster can be prevented. On October 1, 2022, a major disaster occurred at Kanjuruhan Stadium, Malang Regency, East Java, Indonesia, following a Liga 1 Indonesia professional football match between Arema FC and Persebaya, resulting in 712 casualties, including 132 fatalities, 96 serious injuries, and 484 minor injuries. Strengthening the police’s role in disaster prevention at stadiums is essential to minimize the likelihood of similar incidents in the future. This study aims to formulate a disaster prevention strategy from the police role perspective from the case study of the 2024-2025 Liga 1 football match between Persija Jakarta and Dewa United at the Gelora Bung Karno Main Stadium (SUGBK) on September 16, 2024. A qualitative approach was applied through interviews and literature review, analyzed using qualitative SWOT analysis and descriptive analysis. The findings show that Polda Metro Jaya conducted a risk assessment in accordance with existing regulations. The study concludes that the risk assessment performed by the Directorate of Vital Object Protection of Polda Metro Jaya for SUGBK was rated good, ensuring the match could proceed safely. Furthermore, the police play an important role in the disaster prevention strategy at SUGBK. However, current regulation only provides guidelines for risk assessment in sports competitions, and do not yet comprehensively address other mass gatherings such as entertainment or religious events.